Novel 4-aminoquinazoline derivatives induce growth inhibition, cell cycle arrest and apoptosis via PI3Kα inhibition. Issue 8 (1st May 2018) - Fan, Yan-Hua; Ding, Huai-Wei; Liu, Dan-Dan; Song, Hong-Rui; Xu, Yong-Nan; Wang, Jian
Graphical abstract: Highlights: A series of novel 4-aminoquinazoline derivatives were synthesized and characterized. Their antiproliferative activities against cancer cell lines were evaluated. 6b exhibited PI3K inhibitory activity with an IC50 value of 13.6 nM. 6b exhibited potent antiproliferative effects via PI3K/Akt signaling pathway inhibition. Compound 6b induced G1 phase arrest and apoptosis via the mitochondrial pathway. Abstract: Phosphatidylinositol 3-kinase (PI3K) signaling pathway has diverse functions, including the regulation of cellular survival, proliferation, cell cycle, migration, angiogenesis and apoptosis. Among class I PI3Ks (PI3Kα, β, γ, δ), the PIK3CA gene encoding PI3K p110α is frequently mutated and overexpressed in a large portion of human cancers. Therefore, the inhibition of PI3Kα has been considered as a promising target for the development of a therapeutic treatment of cancer. In this study, we designed and synthesized a series of 4-aminoquinazoline derivatives and evaluated their antiproliferative activities against six cancer cell lines, including HCT-116, SK-HEP-1, MDA-MB-231, SNU638, A549 and MCF-7. Compound 6b with the most potent antiproliferative activity and without obvious cytotoxicity to human normal cells was selected for further biological evaluation. PI3K kinase assay showed that 6b has selectivity for PI3Kα distinguished from other isoforms. The western blot assay and PI3K kinase assay indicated that 6b effectively inhibited cell proliferation via suppression of PI3Kα kinase activity with an IC50 of 13.6 nM and subsequently blocked PI3K/Akt pathway activation in HCT116 cells. In addition, 6b caused G1 cell cycle arrest owing to the inhibition of PI3K signaling and induced apoptosis via mitochondrial dependent apoptotic pathway. Our findings suggested that 6b has a therapeutic value as an anticancer agent via PI3Kα inhibition.